"All Skinfolk Ain't Kinfolk": Engaging with Racial Identity and Racism-Based Trauma in Social Work Curricula. Issue 3 (27th May 2021) - Davis, Curtis; Francois, Samantha
ABSTRACT: When the phrase "Social workers cannot be racist" is used, there is not consideration of race, racism, and the detrimental effects of racism. This study includes an exploration of the extent to which social workers have been educated on racism-based trauma. Most participants did not have courses or training on the concept of racism-based trauma in their social work education. They had not been required to engage in the concept and thought of race as a dichotomized construct. Participants expressed the importance of educating themselves, clients, and colleagues on race, racial identity, and the trauma that arises from experiencing racism. These findings helped shape the implications and suggestions for education and training.